MEASUREMENT OF RADIATION EXPOSURE IN FACILITIES FOR RADIOLOGY DIAGNOSTIC AT THE COVID-19 EMERGENCY HOSPITAL IN WISMA ATLET JAKARTA - Irsal, Muhammad; Syuhada, Firdha Adlia; Ananda, Yolanda Pangestu; Putra, Andre Galih Pratama; Syahputera, Muhammad Rizky; Wibowo, Syahputera (Journal of Vocational Health Studies, 2020)
Background: Facility design for radiology diagnostic examination was one of the concerns in the COVID-19 pandemi. This is related to the establishment of emergency department of radiology which were carried out in a very fast pace. Purpose: This study was an effort to the radiation protection for workers and public. Method: Data collection was carried out on 1-29 May 2020 at the COVID-19 Emergency Hospital in Wisma Atlet Jakarta. Result: The assessment for the area 1 was 1 = 22.38 mR /week, in the area was 2 = 5.23 mR /week, in the area 3 = 7.32 mR / week, in the area 4 = 8.67 mR /week. Thus, the exposure received is still within limits safe in the controlled area. Meanwhile, the uncontrolled area will continue to be monitored to ensure that there is no activity. Conclusion: In the  effort of protecting the workers and the public from the radiotion, the principles of radiation protection, distance, time, and shielding should always be implemented.